The distinctive nature of covid-19 vaccines: compensation for potential damages under the legal framework of Lithuanian state in the context of global examples - Mažrimaitė, Andra; Lapis, Vilius; Rimkevičiūtė, Ūla (Vilnius University Open Series, 2023)
The article analyzes legal mechanisms of compensation for damages caused by side effects of COVID-19 vaccines in Lithuania. In particular, draft amendments to the Law on the Rights of Patients and Compensation of the Damage to their Health registered by the Parliament of the Republic of Lithuania in 2021 are evaluated and arguments for the need for further improvement are provided herein. In order to comprehensively assess the nature of the side effects that may be a substantiated cause for damages, pharmaceutical analysis and evaluation of COVID-19 vaccines eligible in Lithuania are analyzed. Analysis of the legal framework and proposals are construed mainly in light of the assessment of global examples. Following throughout evaluation of the question at hand, it is the opinion of the authors of the article that the product liability mechanism is not appropriate in the context of the vaccination program applied in Lithuania and instead „a no-fault compensation model“ shall be adopted that would be funded by a separate (non) State institute/fund in Lithuania.
Keywords: COVID-19 pandemic; vaccines; Constitution; vaccination; side effects; damage compensation; no-fault model